KONSEP PLURALISME PENDIDIKAN ISLAM DI INDONESIA DALAM PERSPEKTIF ABDURRAHMAN WAHID (GUS DUR) - Sari, Eva Sofia; Dozan, Wely (STAI Ma'had Aly Al-Hikam Malang, 2021)
The issue of pluralism has become an important issue specifically discussed throughout the ages and along with the development of the scientific world. Pluralism has been in the spotlight, especially among theological and Islamic thought, so that the issue of pluralism has entered Indonesia and has even reached the implementation of Islamic education. Talking about the term pluralism universally becomes an important point because today's problem is the concept of pluralism is not only a concept that leads to theology. But especially in Indonesia, pluralism is the main knife that must be developed, especially in Islamic education. This paper is here to discuss the pluralism figure in Indonesia, namely Abdurrahman Wahid who is familiarly called GUSDUR the intelligent idol who is one of the figures in Indonesia who gives the concept of pluralism to Islamic education. The focus of this research explores several issues that are quite urgent, namely: First, how is Abdurrahman Wahid's concept of pluralism in Islamic education. Second, what is the basis for Abdurrahman Wahid's thoughts on pluralism in the context of Indonesia. This basic assumption is the main reference which is studied in depth in this research. The type of research is library research with a descriptive analytical research approach that explains the roots of thinking critically. Specifically, it can be concluded that pluralism in education is the most effective institution and media in managing this diversity. The function of education is nothing but an effort to transform the values of a nation. Educational pluralism is an effort to inculcate national and human values, which must be pursued both in the family, community and educational environment. Islamic education in Abdurrahman Wahid's perspective is a sub-system of national education that has quite a big role in the transformation of religious values to students. This should start from Muslims, considering Islam as the majority religion. Changes in the paradigm of Islamic education must be pursued. This is because the paradigm that has been used so far turns out to be more selfish, closed (exclusive), intolerant, and oriented towards personal piety. In facing the plurality of society: multi-ethnic and multi-religious, according to Gus Dur, an educational paradigm that is tolerant, inclusive and oriented towards social piety is needed, not forgetting individual piety.